2016
DOI: 10.1016/bs.ircmb.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of Apoptosis in Cancer

Abstract: Apoptosis is a cellular suicide program that plays a critical role in development and human diseases, including cancer. Cancer cells evade apoptosis, thereby enabling excessive proliferation, survival under hypoxic conditions, and acquired resistance to therapeutic agents. Among various mechanisms that contribute to the evasion of apoptosis in cancer, metabolism is emerging as one of the key factors. Cellular metabolites can regulate functions of pro- and antiapoptotic proteins. In turn, p53, a regulator of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(93 citation statements)
references
References 236 publications
(286 reference statements)
0
93
0
Order By: Relevance
“…Given that cancer cell proliferation and apoptosis are closely linked with glycolysis (Matsuura et al, 2016), we examined whether AT-I can be used to induce a metabolic shift in CRC cells. We found that after AT-I treatment, there was a significant dose-dependent decrease in glucose consumption by the CRC cells ( Figure 3A).…”
Section: At-i Mediated Suppression Of Glycolysis In Crc Cells Via a Rmentioning
confidence: 99%
“…Given that cancer cell proliferation and apoptosis are closely linked with glycolysis (Matsuura et al, 2016), we examined whether AT-I can be used to induce a metabolic shift in CRC cells. We found that after AT-I treatment, there was a significant dose-dependent decrease in glucose consumption by the CRC cells ( Figure 3A).…”
Section: At-i Mediated Suppression Of Glycolysis In Crc Cells Via a Rmentioning
confidence: 99%
“…Recently, increasing evidence has shown that cancer does not occur in mice with p53 mutations, which nonetheless retain p53 activity for regulation of energy metabolism; this suggests that p53 activities in the context of metabolic regulation may be critical for suppression of tumorigenesis [51]. Numerous cancer studies of the metabolic pathways regulated by p53 have been conducted recently [52][53][54]. As noted by Gomes et al in their review article, p53 activation is involved in the complex process of reprogramming cancer glucose metabolism [55].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a form of programmed cell death. Insu cient apoptosis is associated with neoplastic diseases [43]. However, the speci c molecular mechanism between the differentially expressed genes and potential pathways remained unclear, which provide new clues and molecular targets for identi cation and speci c treatment of GC with LN metastasis.…”
Section: Discussionmentioning
confidence: 99%